Quale possibile ruolo delle PMI nello sviluppo del marketing territoriale? Analisi del caso “Land of Value (LOV)” - Gregori, Gian Luca; Temperini, Valerio; Perna, Andrea (Piccola Impresa / Small Business, 2013)
This paper focuses on the theme of territorial marketing from the perspective of local SMEs, with the aim to highlight the possible role that these organizations can play in promoting their territory. Particularly, the research involves the “Gruppo Loccioni”, a medium business operating in the high technology sector, which has developed a network that involves local small business and operators of different sectors (agriculture, tourism, culture, accommodation and catering services, commerce, etc..) in order to offer a particularly positive experience to its visitors. The basic idea is that providing a welcoming environment can combine the aims of business with the features peculiar of the geographic area. The study therefore brings to stress the possible convergence between territorial marketing and relationship marketing.